Configuration and Analysis Link-State Open Shortest Path First Routing Performance Multi-Area - Nur Hayati; Ratih Titi Komala Sari; Dede Wandi (SMARTICS Journal, 2021)
Open Shortest Path First (OSPF) is a routing protocol that uses a link-state algorithm to build and calculate the best path to all known destinations. The link-state algorithm is also known as the Dijkstra algorithm or Shortest Path First (SPF) algorithm. The Dijkstra algorithm applied in the OSPF protocol to choose the best route. That a data packet must take from an origin address to arrive at the destination address with the least cost metric. The results showed that using the OSPF routing protocol between the Head Office and Branch can communicate with each other by sending each OSPF database to each router where the maximum data transmission value is 1-millisecond sending data successfully reaches100%